“The Power of Language”: Young People in Greece as “Scapegoats” in Covid-19 Crisis - Alexopoulou, Sofia (HAPSc Policy Briefs Series, 2021)
Governments around the globe take measures to protect citizens against the coronavirus threat. At the end of the day, security becomes a top priority issue and therefore is included in almost every policy agenda. In light of this, some governments seem to victimize certain social groups when they are incapable of addressing successfully the health crisis of Covid-19. An indicative example is the Greek government’s tactic (New Democracy Party) to blame young people for the spread of the virus, while the real ‘culprit’, according to some (Tziantzi & Papadopoulou, 2020), was the restart of tourist industry that resulted in a sharp rise of the Corona incidents. In doing so, language was the key ‘vehicle’ for this purpose along with statistical numbers, but the latter is a whole different discussion that this paper is not going to open. On the contrary, this paper constitutes a problematization on the usage of language for political reasons. Language is not a neutral tool but plays the games of political elites, while it has the power to create new scapegoats. Is this a wise political choice when Greek society encounters so many problems related to the Covid-19 pandemic? Logical reasoning says no. Will young people be the only exception to this rule? Certainty not, today new scapegoats come into light: citizens who refuse to be vaccinated and/or the sprayed’ ones.